The 26th Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2004.1404039
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Lymphatic Vessel Structure

Abstract: Lymphatic vessels transport excess interstitial fluid from the low-pressure tissues to the higher pressure veins. The basic structural unit of lymphatic vessels is the lymphangion, a segment of the vessel separated by two unidirectional valves. Lymphangions cyclically contract like ventricles and can actively pump lymph. Lymphangions, as conduit vessels, also can act as arteries, and resist lymph flow. Functional parameters such as pressures, flow, and efficiency are determined by structural parameters like le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This study revealed that the average flow through a lymphatic vessel remained unaffected by the propagation direction of its contractile waves. Although these models were evaluated numerically, they allowed manipulation of parameters, such as length and contractility, that cannot be experimentally controlled (32). The complexity of numerical solutions, however, increases dramatically when an attempt is made to model more than a few lymphangions because of the large number of required parameters.…”
mentioning
confidence: 99%
“…This study revealed that the average flow through a lymphatic vessel remained unaffected by the propagation direction of its contractile waves. Although these models were evaluated numerically, they allowed manipulation of parameters, such as length and contractility, that cannot be experimentally controlled (32). The complexity of numerical solutions, however, increases dramatically when an attempt is made to model more than a few lymphangions because of the large number of required parameters.…”
mentioning
confidence: 99%
“…While there have been multiple computer models phenomenologically incorporating both phasic and tonic contractions of lymphatic muscle (Caulk et al 2016;Caulk et al 2015;Kunert et al 2015;Razavi et al 2020;Razavi et al 2017), the different effects of the contraction types were the focus of only one series of computational modelling papers. This model used the time-varying elastance model of the heart combined with the transmission line equations for blood vessels (Quick et al 2008;Venugopal et al 2007;Venugopal et al 2010;Venugopal et al 2004;Venugopal et al 2003).…”
Section: Introductionmentioning
confidence: 99%